Synthesis and Characterization of Surfactant Capped Copper Nanoparticles Using Natural Vitamin - Varun Kumar, B.; Parveen Taj, Y.; Hussain Reddy, K. (Asian Journal of Chemistry, 2020)
Copper nanoparticles (CuNPs) have captivated amazing and renewable interest in recent years due to their fascinating features. In present investigation, CuNPs were produced by reducing copper sulphate with ascorbic acid (vitamin C) in aqueous medium without inert gas insulation at low temperature (80 ºC). In present synthetic procedure, a native vitamin C was applied as insulating agent to prevent oxidation of nascent CuNPs during the process and in storage. Triton X-100 was added that worked both as a size controller and as a capping agent. The CuNPs were characterized by UV-visible and FT-IR spectroscopies, powder X-ray diffraction (PXRD) and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDX). Optical properties of Cu nanoparticles were explored using UV-vis spectroscopy. FT IR was employed to uncover the bonding between copper nanoparticles and Triton X-100. The CuNPs were discerned by PXRD and SEM-EDX Techniques. From the major diffraction peaks, the average particle size is determined using Debye-Scherer equation and it is found to be about 15 nm. It is hoped that the present results would pave a way for developing plans for the production of nascent CuNPs in the absence of inert gas insulation.